SIRT1 haplo-insufficiency results in reduced cortical bone thickness, increased porosity and decreased estrogen receptor alpha in bone in adult 129/Sv female mice - Artsi, Hanna; Cohen-Kfir, Einav; Shahar, Ron; Kalish-Achrai, Noga; Lishinsky, Natan; Dresner-Pollak, Rivka (Frontiers in Endocrinology, 2022)
Sirtuin 1 (SIRT1) is a key player in aging and metabolism and regulates bone mass and architecture. Sexual dimorphism in skeletal effects of SIRT1 has been reported, with an unfavorable phenotype primarily in female mice. To investigate the mechanisms of gender differences in SIRT1 skeletal effects, we investigated femoral and vertebral cortical and cancellous bone in global Sirt1 haplo-insufficient 129/Sv mice aged 2,7,12 months lacking Sirt1 exons 5,6,7 (Sirt1+/Δ) and their wild type (WT) counterparts. In females, femoral bone mineral content, peak cortical thickness, and trabecular bone volume (BV/TV%), number and thickness were significantly lower in Sirt1+/Δ compared to WT mice. Increased femoral cortical porosity was observed in 7-month-old Sirt1+/Δ compared to WT female mice, accompanied by reduced biomechanical strength. No difference in vertebral indices was detected between Sirt1+/Δ and WT female mice. SIRT1 decreased with aging in WT female mice and was lower in vertebrae and femur in 18- and 30- versus 3-month-old 129/Sv and C57BL/6J female mice, respectively. Decreased bone estrogen receptor alpha (ERα) was observed in Sirt1+/Δ compared to WT female mice and was significantly higher in Sirt1 over-expressing C3HT101/2 murine mesenchymal stem cells. In males no difference in femoral indices was detected in Sirt1+/Δ versus WT mice, however vertebral BV/TV%, trabecular number and thickness were higher in Sirt1+/Δ vs. WT mice. No difference in androgen receptor (AR) level was detected in Sirt1+/Δ vs. WT male mice. Bone SIRT1 was significantly lower in male compared to female WT mice, suggesting that SIRT1 maybe more significant in female than male skeleton. These findings demonstrate that 50% reduction in SIRTirt1 is sufficient to induce the hallmarks of skeletal aging namely, decreased cortical thickness and increased porosity in female mice, highlighting the role of SIRT1 as a regulator of cortical bone quantity and quality. The effects of SIRT1 in cortical bone are likely mediated in part by its regulation of ERα. The age-associated in bone SIRT1 positions SIRTirt1 as a potential therapeutic target to ameliorate age-related cortical bone deterioration in females. The crosstalk between ERα, AR and SIRT1 in the bone microenvironment remains to be further investigated.